Brain White Matter Correlates of Creativity in Schizophrenia: A Diffusion Tensor Imaging Study - Sampedro, Agurne; Peña, Javier; Ibarretxe-Bilbao, Naroa; Cabrera-Zubizarreta, Alberto; Sánchez, Pedro; Gómez-Gastiasoro, Ainara; Iriarte-Yoller, Nagore; Pavón, Cristóbal; Ojeda, Natalia (Frontiers in Neuroscience, 2020)
The relationship between creativity and psychopathology has been a controversial research topic for decades. Specifically, it has been shown that people with schizophrenia have an impairment in creative performance. However, little is known about the brain correlates underlying this impairment. Therefore, the aim of this study was to analyze whole brain white matter (WM) correlates of several creativity dimensions in people with schizophrenia. Fifty-five patients with schizophrenia underwent diffusion-weighted imaging on a 3T magnetic resonance imaging machine as well as a clinical and a creativity assessment, including verbal and figural creativity measures. Tract-based spatial statistic, implemented in FSL, was used to assess whole brain WM correlates with different creativity dimensions, controlling for sex, age, premorbid IQ, and medication. Mean fractional anisotropy in frontal, temporal, subcortical, brainstem, and interhemispheric regions correlated positively with figural originality. The most significant clusters included the right corticospinal tract (cerebral peduncle part) and the right body of the corpus callosum. Verbal creativity did not show any significant correlation. As a whole, these findings suggest that widespread WM integrity is involved in creative performance of patients with schizophrenia. Many of these areas have also been related to creativity in healthy people. In addition, some of these regions have shown to be particularly impaired in schizophrenia, suggesting that these WM alterations could be underlying the worse creative performance found in this pathology.